Concept of Treatment of Infectious Disease in Ayurveda - Mishra , Avinash Kumar; Pandey, Bashisth (Journal of Neonatal Surgery, 2025)
Ayurveda, though lacking a dedicated chapter on infectious diseases, identifies conditions equivalent to communicable illnesses under accounts of sankramika roga, aupasargika vyadhi, and krimi roga. These categories encompass microbial and parasitic agents and recognize transmission via contact, shared eating or sleeping, fomites, and inhalation. According to classical understanding, external pathogens initiate disease only after disrupting the body's internal doshas; thus, pathogenesis is viewed through the six-stage (ṣaṭkriyakala) model, emphasizing imbalance in doshas, dhatus, and malas. Treatment focuses on three primary strategies: purificatory expulsion therapies (such as emesis, purgation, enema, nasal cleansing or bloodletting), the use of heat and bitter quality herbs to impede pathogen proliferation by altering host terrain, and prevention by avoiding causative exposure. In sum, Ayurveda acknowledges microbial causation but prioritizes restoring internal equilibrium and strengthening the host over directly targeting pathogens, offering a host centric alternative paradigm in traditional medical theory